2014
DOI: 10.1002/ece3.1110
|View full text |Cite
|
Sign up to set email alerts
|

Identifying species of moths (Lepidoptera) from Baihua Mountain, Beijing, China, using DNA barcodes

Abstract: DNA barcoding has become a promising means for the identification of organisms of all life-history stages. Currently, distance-based and tree-based methods are most widely used to define species boundaries and uncover cryptic species. However, there is no universal threshold of genetic distance values that can be used to distinguish taxonomic groups. Alternatively, DNA barcoding can deploy a “character-based” method, whereby species are identified through the discrete nucleotide substitutions. Our research foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
(123 reference statements)
4
14
0
2
Order By: Relevance
“…Moreover, the maximum intrasequence variation recorded was lower than the distance with NN for different species of agricultural pests. Liu et al (2014) worked on Noctuidae and Arctiidae family and observed the similar results. Similar results were attained by Gopurenko et al (2013) during identification of leafhoppers, treehoppers, and planthoppers (Hemiptera: Auchenorrhyncha) via DNA barcoding.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, the maximum intrasequence variation recorded was lower than the distance with NN for different species of agricultural pests. Liu et al (2014) worked on Noctuidae and Arctiidae family and observed the similar results. Similar results were attained by Gopurenko et al (2013) during identification of leafhoppers, treehoppers, and planthoppers (Hemiptera: Auchenorrhyncha) via DNA barcoding.…”
Section: Discussionsupporting
confidence: 55%
“…This method proposes a standard definition of the barcode gap and can be used to partition the dataset into candidate species, even when two distributions overlap (see Liu et al, 2014). Sequences of each dataset (ITS2, N = 20, 13 species; rpoC1, N = 11, 4 species; trnH-psbA, N = 20, 6 species) were uploaded to http://wwwabi.snv.jussieu.fr/public/abgd/abgdweb.html.…”
Section: Sequence Analysis and Species Identificationmentioning
confidence: 99%
“…The ABGD is a tool that automatically finds the barcode gap, and can be used when two distributions overlap to partition the dataset into candidate species (Puillandre et al, 2012;Liu et al, 2014). In this study, the ABGD method for both initial and recursive partition for the trnH-psbA dataset (N = 20, six species) resulted in six groups with P ranging from 0.001 to 0.0129, three groups with P at 0.0215, and two groups with P ranging from 0.0359 to 0.1000 (Table 5).…”
Section: Barcoding Gap Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the inception of DNA barcoding as a molecular technique for species identification (Hebert et al 2003), many studies have been targeted to know the region-specific lepidopteran biodiversity (Lukhtanov et al 2009;Dinca et al 2011;deWaard et al 2011;Hausmann et al 2011Hausmann et al , 2013Wilson et al 2013;Huemer et al 2014;Liu et al 2014;Zahiri et al 2014). Several studies have been shown to resolving the taxonomic quest and the dilemma in lepidopteran systematics (Hajibabaei et al 2006;Burns et al 2008;Hausmann et al 2009;Mutanen et al 2012;Jiang et al 2017).…”
Section: Introductionmentioning
confidence: 99%